Progressive Leadership : challenging the theory of the firm in the 21st century. - Park, Greg (Emerald Publishing Limited, 2022)
Progressive Leadershipaddresses the diminishing and increasingly dysfunctional contribution of firm leadership in the operational effectiveness, performance, and survival of the firm in the business context of the twenty-first century.- Resumé vydavatel
Keywords: řídící práce; vůdcovství; management; leadership; elektronické knihy; monografie; electronic books; monographs